Effect of high intakes of protein-only and carbohydrate-only on plasma metabolites and hormones, in addition to nitrogen excretion - Clauss, Matthieu; Puissant, Claire; Bastani, Nasser Ezzatkhah; Nielsen, Lotte L. K.; Skålhegg, Bjørn Steen; Jeppesen, Per Bendix; Jensen, Jørgen (Frontiers in Endocrinology, 2025)
BackgroundHormonal and metabolic responses to high protein intake are not well understood. The aims of this study were to compare the metabolic and hormonal responses to isocaloric intakes of whey protein alone versus carbohydrate alone. Additionally, we measured urinary nitrogen excretion as a marker of protein degradation.MethodsFourteen young, healthy, moderate-to-well-trained participants (VO2max 50.6 ± 2.9 mL·kg-1·min-1; mean ± SEM) reported in the morning after an overnight fast. In a double-blinded, randomized, balanced cross-over design, participants consumed isoenergetic test drinks containing either 1.2 g·kg-1 of whey protein alone (PRO) or carbohydrate alone (CHO) on separate days. They recorded their dietary intake the day before and during the intervention to repeat them across the second trial day. Blood samples were collected at regular intervals after drink ingestion. Urine was collected throughout the testing period in six consecutive batches.ResultsAfter CHO intake, plasma glucose levels increased, and certain plasma amino acid concentrations decreased. Following PRO intake, plasma glucose decreased, and plasma amino acids increased. Insulin concentrations increased following ingestion of both CHO and PRO (time effect, p<0.001), with a greater increase in CHO (drink effect, p<0.001). Plasma GLP-1 and GIP concentrations increased in both conditions (time effect, p<0.001). Plasma GLP-1 increased more in PRO than in CHO (drink effect, p<0.001), whereas plasma GIP increased more in CHO than in PRO (drink effect, p<0.001). Urinary nitrogen excretion over the 24 hours following drink ingestion was significantly higher in PRO (p<0.001), particularly between 2 to 8 hours after intake (p<0.001).ConclusionsCHO increased plasma insulin more than PRO. The PRO induced insulin response was independent of glucose and mediated by the increase in plasma amino acids and GLP-1. Interestingly, the GLP-1 response was larger following PRO and remained elevated after 240 minutes, whereas the GIP response was larger following CHO. Additionally, protein-only ingestion increased urinary nitrogen excretion, mainly between 2 to 8 hours after intake, with elevated excretion persisting up to 24 hours.